Root adaptation and ion selectivity affects the nutritional value of salt-stressed hydroponically grown baby-leaf Nasturtium officinale and Lactuca sativa - Fernández, Juan A.; Niñirola, Diana; Ochoa, Jesús; Orsini, Francesco; Pennisi, Giuseppina; Gianquinto, Giorgio; Egea-Gilabert, Catalina (Agricultural and Food Science, 2016)
The response of watercress (Nasturtium officinale L.) to salinity has been scarcely addressed in literature despite its growing importance in the baby-leaf market and its wide cultivation in salt-affected agricultural regions. This work evaluates the effect of salinity (2.5, 5 and 10 dS m-1) on productive and quality features of watercress compared with another crop widely cultivated for the baby-leaf sector (lettuce, Lactuca sativa). In watercress, a linear relationship (R2=0.75) was observed between yield decrease and Cl– accumulation in leaves, whereas yield was not affected by salinity in lettuce. NaCl application increased Na+ accumulation at the expense of Ca2+ uptake in the leaf tissues of both crops, but also of K+ in watercress. Health-related features were improved by salinity (e.g. increased phenolics and reduced nitrates), especially in watercress, with limited sensorial quality evaluation effects.